Clinical suppression of bradycardia dependent premature ventricular contractions by the potassium channel opener nicorandil. Issue 1 (1st January 1998) - Takahashi, Naohiko; Ito, Morio; Saikawa, Tetsunori; Arita, Makoto; Fujino, Takehiko; Kagiyama, Hiroshi; Fukumoto, Teruo; Sakata, Toshiie
Abstract : Objective: To assess the clinical antiarrhythmic effect of nicorandil, a potassium channel opener, on premature ventricular contractions. Design and patients: The effect of oral nicorandil (15 to 60 mg daily for four weeks) on premature ventricular contractions was investigated in 20 patients (11 female, nine male, mean (SD) age 63 (17) years) who underwent 24 hour ambulatory ECG. Patients were classified into two groups based on the relation between the frequency of premature ventricular contractions and heart rate: (1) those with a positive correlation (n = 9); and (2) those with a bidirectional correlation (n = 11), characterised by an increased frequency of premature contractions at low heart rates and a decreased frequency at high heart rates. Results: Nicorandil reduced the frequency of premature ventricular contractions by 75% in five patients in group 2, but was not effective in any patient in group 1. The heart rate at which the frequency of premature ventricular contractions peaked was significantly lower in the five responders in group 2 than in the six non-responders (63.2 (3.7) v 76.3 (12.4) beats/min, p < 0.05). Conclusions: Nicorandil may suppress premature ventricular contractions when they occur mainly at a low heart rate.